SISTEM PENJUALAN DENGAN PEMOTONGAN DI BAWAH HARGA PASAR MENURUT HUKUM ISLAM - Saleh, Muhammad; Sani, Abdullah; Prasetiyorini, Pudhak; Wulandari, Bernadetta Tjandra; Mahardika, Swadia Gandhi (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study aims to investigate the perspective of Islamic law on the implementation of price reduction systems in the marketing of adult and children’s clothing, as well as men’s and women’s apparel. The research explores the conditions under which discounted goods are permissible according to Islamic principles. A qualitative method was employed, analyzing relevant Islamic legal texts and contemporary market practices. The findings indicate that Islamic law permits price reduction systems, provided they meet specific conditions. The seller may set a base price and offer discounts, which must be agreed upon by both parties involved in the transaction. The process must ensure mutual consent without coercion or fraud (gharar). The transaction proceeds with a sale and purchase contract if an agreement is reached. Otherwise, the transaction does not occur. This study contributes to understanding permissible marketing strategies within Islamic economics, highlighting the importance of fairness and mutual agreement in trade practices.